Contribution to the Inventory and Classification of Aquatic birds as natural enemies of fish in the Lake Dam 16th of Tishreen (Latakia University Journal -Biological Sciences Series, 2020)
This study was conducted during July 2018 to July 2019 at an average of two visits per month in the Lake Dam 16th of Tishreen in two sites, fish farm (floating cages) and reservoir (near agricultural land). The results showed that there are five species of aquatic birds belong to three orders and three Families namely; Great White Egret, Egretta alba L.1758, little White Egret, Egretta garzetta, Gray Egret Ardea cinerea, Sura, Fulica atra and Cormorant, Phalacrocorax aristotelis. As a result of monitoring and observation of each in the two selected sites, 1969 and 1222 scenes were recorded in the first and second sites, respectively. The Small White Egret was recorded the highest percentage of frequency near to the cages, while the Great White Egret was the second. The number of recorded individuals was varied according to the months of the year. It was 126 individuals for Cormorants in January 2019, 365 for Small Egret in May 2019 while Gray Egret did not notice during July, August, September and October of 2018. Some ecological factors, specific richness coefficient, degree of stability, variation coefficient, dominance coefficient and species richness factor showed that the most abundance species were Large White Egret and Small White Egret (with 50% for each) followed by Fulica atra , Cormorants and Grey heron (with 37.5% for each).   أجري البحث خلال الفترة من تموز2018 م إلى تموز 2019م بمعدل جولتين شهرياً  في بحيرة 16سد تشرين ، أظهرت النتائج وجود خمسة أنواع من الطيور المائية منتمية إلى ثلاث رتب و ثلاث فصائل, وهي: البلشون الأبيض الكبير Egretta alba , البلشون الأبيض الصغير Egretta garzetta , البلشون الرمادي Ardea cinerea, طائر الغرة Fulica atra , وطائر الغاق Phalacrocorax aristotelis . نتيجة للرصد والمراقبة في الموقعين المختارين من البحيرة هما: المزرعة السمكية (الأقفاص العائمة), الخزان (قرب الأراضي الزراعية), سجل /1969/ فرداً و /1222/ فرداً في الموقعين الأول و الثاني على التوالي, وسجل طائر البلشون الأبيض الصغير أعلى نسبة مصادفة حول الأقفاص, بينما شغل طائر البلشون الأبيض الكبير المرتبة الثانية. تباينت أعداد الأفراد المسجلة تبعاً لأشهر السنة, فكانت /126/ فرداً لطائر الغاق في شهر كانون الثاني, و/365/ فرداً لطائر البلشون الأبيض الصغير في شهر أيار بينما لم يظهر البلشون الرمادي خلال أشهر تموز, آب, أيلول , تشرين الأول( (2018م. كما درست بعض المعاملات البيئية (معامل الغنى النوعي, معامل السيادة, درجة الثبات, معامل الاختلاف, دليل التنوع) فتبين أن أكثر الطيور ثباتاً خلال جميع الجولات تقريباً هما البلشون الأبيض الكبير و البلشون الأبيض الصغير بدرجة ثبات 50 % يليهما طائر الغاق و الغرة و البلشون الرمادي بـ 37.5%.